DIURON, METHOMYL AND MCPA ADSORPTION BY ACTIVATED CARBONS FROM ANGOLAN LIGNOCELLULOSIC PRECURSORS - Tchikuala, Emilio (2018)
This work reports the production of activated carbons from novel precursors, namely wood produced in Angola (Benguela region), and its application to remove pollutants from aqueous solutions, namely Diuron, Methomyl and MCPA. At present, Angola has a considerable amount of waste of wood, either from the cutting of trees for residential areas, factory, mining, oil and gas, which are abandoned, suffering a slow degradation.